The root-lesion nematode, Pratylenchus penetrans , affects early growth and physiology of grafted M.9, G.41 and G.935 apple rootstocks similarly under field microplot conditions - King, Lindsay; Munro, Paige; Xu, Hao; Jones, Melanie; Forge, Thomas (Plant disease, 2024)
The root-lesion nematode, , is a ubiquitous parasite of roots of temperate fruit trees. It affects early growth of trees replanted into former orchard sites where populations have built up, and may contribute to decline complexes of older trees. Most British Columbia, Canada apple acreage is planted with M.9 rootstock, but growers are increasingly considering Geneva-series rootstocks such as G.41 and G.935. Among these rootstocks, responses to , specifically, are poorly known. To compare the resistance and tolerance to of G.41, G.935 and M.9 rootstocks ('Ambrosia' scion), a field microplot experiment was established in spring of 2020 at the Summerland Research and Development Centre. The experimental design was a 2 x 3 factorial combination of: inoculation (+/-) and rootstock (G.41, G.935, M.9), with 20 replicate microplots of each of the six treatment combinations arranged in a randomized complete block design. The inoculum was 5400 nematodes per microplot (54 L-1 soil), which is below commonly accepted damage thresholds. Though population densities were lower for the G.41 rootstock by the end of the 2021 growing season, the effects of were similar among rootstocks. In the establishment year (2020), caused significant reductions in aboveground growth. In 2021, shoot growth and root weight were reduced by . The nematode also reduced rates of leaf gas exchange and stem water potential. These data suggest that while G.41 and G.935 may have other horticultural benefits over M.9, they are equally susceptible to at the early stages of tree growth.